Konstruksi Realitas Sosial Anggota Komunitas Penggemar Boyband Exo Jakarta - Zulfa Ayundia Nabila; Davis Roganda Parlindungan (UNIVERSITAS KALBIS, 2022)
The EXO boyband community or who have an EXO-L nickname is a community that was formed because of the large enthusiasm of Kpop fans to be able to express their love for their idols. Boyband EXO is a boyband from South Korea consisting of nine members formed by S.M. Entertainment.The purpose of this study was to determine the process social construction of reality from EXO boyband community members in Jakarta. This research approach uses a qualitative approach with the Case Study analysis method. The theory used is the theory Social Construction of Reality proposed by Peter L. Berger and Thomas Luckmann. The results of this study show that the social construction of reality experienced by members of the EXO or EXO-L boy band community begins with knowing Kpop, knowing the EXO boy band, joining the EXO-L community and making adjustments, interacting with fellow members, to identify themselves with their members in EXO boyband community.